Microstructure of Calcium Stearate Matrix Pellets: A Function of the Drying Process. Issue 11 (26th August 2013) - Schrank, Simone; Kann, Birthe; Windbergs, Maike; Glasser, Benjamin J.; Zimmer, Andreas; Khinast, Johannes; Roblegg, Eva
<x xml:space="preserve">Abstract</x> Drying is a common pharmaceutical process, whose potential to modify the final drug and/or dosage form properties is often underestimated. In the present study, pellets consisting of the matrix former calcium stearate (CaSt) incorporating the active pharmaceutical ingredient ibuprofen were prepared via wet extrusion and spheronization. Subsequent drying was performed by either desiccation, fluid‐bed drying, or lyophilization, and the final pellets were compared with respect to their microstructure. To minimize the effect of solute ibuprofen molecules on the shrinking behavior of the CaSt, low ibuprofen loadings were used, as ibuprofen is soluble in the granulation liquid. Pellet porosity and specific surface area increased during desiccation, fluid‐bed drying, and lyophilization. The inlet‐air temperature during fluid‐bed drying affected the specific surface area, which increased at lower inlet‐air temperatures rather than the pellet porosity. The in vitro dissolution profiles were found to be a nonlinear function of the specific surface area. Overall, the microstructure, including porosity, pore size, and specific surface area, of CaSt pellets was a strong function of the drying conditions. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:3987–3997, 2013